Relationship of Soil Physicochemical Properties and Existence of Phytophthora sp. in Pineapple Plantations - Deva Aziz Nanda Martin; Ali Rahmat (Indonesian Journal of Science and Technology, 2017)
One of the tropical fruits with high economic value is pineapple. Pineapple plantation has several limitations, especially in cultivating period and diseases caused by Phytophthora sp. (called heart rot disease). The spread of Phytophthora sp. in pineapple plantation is influenced by physical of soil (called as soil borne pathogen). Here, the purpose of this study was to examine physical properties of soil (compaction), specifically on heart rot disease in pineapple plantation. We used pineaple farm locating in Central Lampung, Indonesia. In this paper, we analyzed the disease impact from the soil compaction point of view. We investigated the difference between soil samples with and without sick plant. The results showed that the disease area were affected by Phytophthora sp. area have high soil compaction. Indeed, this soil condition is good for growing Phytophthora sp.